Digital Leadership and Teachers’ Performance: Basis for a Proposed Training Program - Dela Rosa, Marivic Agbuya (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study aimed to determine the digital leadership and performance of teachers in Marikina City. The paper utilized a descriptive research design to accomplish the investigation and validate the level of digital leadership of school administrators and the performance of teachers. The main objective of the study was to describe the nature of a situation as it exists at the time of the study and to explore the cause of a particular phenomenon. The statistical treatments of data used were weighted mean, t-test, and Pearson r correlation. The extent of level of digital leadership as perceived by the school administrators in public secondary schools in Marikina was very knowledgeable. The extent level on digital leadership as perceived by the teachers in public secondary schools in Marikina was very knowledgeable. There was a slight correlation between the digital leadership and teachers’ performance. The school administrators should encourage themselves and be motivated to pursue digital learning development that would increase their techno-leadership style.